If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + 4 + 2t + -5t = 1 Reorder the terms: 4 + 4t + 2t + -5t = 1 Combine like terms: 4t + 2t = 6t 4 + 6t + -5t = 1 Combine like terms: 6t + -5t = 1t 4 + 1t = 1 Solving 4 + 1t = 1 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 1t = 1 + -4 Combine like terms: 4 + -4 = 0 0 + 1t = 1 + -4 1t = 1 + -4 Combine like terms: 1 + -4 = -3 1t = -3 Divide each side by '1'. t = -3 Simplifying t = -3
| (7x-8)(4x+3)=0 | | (8x+9)(3x-7)=0 | | 2(6q-2)= | | 3x+6-2x+9=4x-18 | | -x+x+30=0 | | 8x-9=2-3x | | -7y+5=8y+6 | | 4x-7=18-x | | 10x^2-9x-7=0 | | 4x-7=14-3x | | 4x-10=5-x | | 14=z+14 | | 8x-15=7-3x | | 8x^2+6x-35= | | 0=-16t^2+60t | | z^2-26z-87=0 | | 15z-6z=36 | | m-2-7=11 | | 5y-y+6y= | | X^2+4x=192 | | 36-2x=36.444444444 | | 2x^3-9x^2+4x=0 | | 90=1.5t^2+8 | | 4t^2-7t-8=0 | | y=20x+5 | | y=20+5 | | 7x+3y=12 | | v^2-13v+36=0 | | y^4-13y^2+36=0 | | 36-2x=36.444444 | | 9x-6x-7x-2x=36 | | 4+6*5= |